Republic of Moldova : Request for an Extended Arrangement Under the Extended Fund Facility and an Arrangement Under the Extended Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Moldova. (IMF Staff Country Reports; Country Report ;, 2016)
Since late 2014, Moldova's economy has been hit by a number of domestic and external shocks. Chief among them is the exposure of extensive and well-orchestrated fraud in the banking system, resulting in the closure of three banks at a public cost of 10 percent of GDP. During the following period, confidence collapsed, external concessional financing largely froze, and international reserves fell by one-third, prompting significant tightening of monetary conditions. Domestic political turmoil, marked by three changes in government, constrained solutions and delayed collaboration with the international community on possible financial support.